In Situ-Forming Microparticles for Controlled Release of Rivastigmine: In Vitro Optimization and In Vivo Evaluation - Mohamed Haider (Pharmaceuticals, 2021)
In this work, sucrose acetate isobutyrate (SAIB) and polylactic co-glycolic acid (PLGA) were used alone or in combination as a matrix-former (MF) to prepare long-acting injectable rivastigmine (RV) in situ-forming microparticles (ISM). RV-ISM were prepared by the emulsification of an internal phase, containing the drug and the matrix former(s), into an external oily phase containing a stabilizer. The statistical design, Central Composite Design (CCD), was adopted as a quality by design (QbD) approach to optimize the formulation of RV-ISM systems. The fabricated RV-ISM systems was designed to minimize the initial burst drug release and maximize the sustainment of RV release from the ISM and ease of injection. The influence of critical formulation variables such as the matrix-former to drug (MF/D) ratio and SAIB to PLGA (S/P) ratio in the internal phase with respect to critical quality attributes (CQAs), such as the percentage drug release within the first day (Q1), the time required for 50% drug release (T50%) and the rate of injection, were studied using the CCD. The optimal RV-ISM system with the highest desirability value (0.74) was predicted to have an MF/D ratio of 11.7:1 (w/w) and an S/P ratio of 1.64:1 (w/w). The optimal RV-ISM system was assessed for its release profile, injectability, rheological properties, morphology, effect on cell viability, tolerance to γ-sterilization and in vivo performance in male albino rabbits. In vitro release studies revealed that the optimal RV-ISM system released 100% of its drug content throughout a release period of 30 days with only 15.5% drug release within the first day (Q1) and T50% of 13.09 days. Moreover, the optimal system showed a high injection rate of 1.012 mL/min, pseudoplastic flow, uniform spherical globules with homogenous particle size, minimal cytotoxicity and high tolerability to γ-sterilization. In vivo pharmacokinetic (PK) studies revealed that the rate of absorption of RV from the optimal RV-ISM system was controlled compared to a drug solution following either intramuscular (IM) or subcutaneous (SC) injection. Furthermore, the optimal RV-ISM was found to follow flip-flop PK with poor correlation between in vitro release and in vivo findings. These findings suggest that the optimal RV-ISM is a promising tool to achieve a sustained release therapy for RV; however, further investigation is still required to optimize the in vivo performance of RV-ISM.